Mathematical simulation of the phototransistors - Julija Anilionienė (Lietuvos Matematikos Rinkinys)
There are presented the model of the phototransistors and evaluated their non-linearity‘s. For simulation non-linearity‘s influence in a signal distortion the functional Voltera series are developed.